(untitled) (Journal of Applied Learning and Teaching, 2024)
The social psychology of justice has been a relatively under-researched topic in academic circles over the last few decades, especially in developing countries such as Tunisia. This paper endeavors to address this research gap by carrying out a survey on university students who are affiliated with the Faculty of Economics and Management of Nabeul (FSEGN), a distinguished public college situated in the governorate of Nabeul, Tunisia. The results obtained from the structural equation modeling (SEM) analysis using AMOS software version 23 showed that distributive justice and emotional support significantly and positively influence school grades and students’ academic performance. Furthermore, it was found that emotional support partially mediates the link between distributive justice and university students’ academic performance. The study emphasizes the crucial role of emotional support in the link between distributive justice and university students’ academic performance. These results have many implications for higher education institutions, their teachers, and scholars on sustainable higher education.